Integrating Islamic Values and Behavioral Management in Pesantren Student Development - Zainal Abidin; Akhmad Fauzi Hamzah; Ahmad Qusairi; Fadhel Mubarak (JIEMAN: Journal of Islamic Educational Management, 2026)
Islamic boarding schools (pesantren) face growing challenges in preserving traditional Islamic values while responding to educational modernization and changing student behavior. This study examines how the Qismu Riayah division at Darullughah Wadda'wah Islamic Boarding School integrates Islamic values with contemporary student behavior management to support holistic student development. A qualitative case study design was employed, with data collected through semi-structured interviews involving 37 informants, non-participant observations, and institutional document analysis. The findings reveal that Qismu Riayah functions not only as a disciplinary unit but also as a structured mentoring and character-development system. Traditional Islamic values, including ikhlas (sincerity), adab (ethics), discipline, and collective responsibility, are embedded in daily mentoring, dormitory supervision, and counseling, while contemporary approaches such as peer mentoring, positive reinforcement, and restorative practices strengthen students' behavioral and emotional development. The study demonstrates that Islamic values and modern student management practices are complementary rather than contradictory. It contributes to Islamic educational management by proposing an integrative model that bridges traditional pesantren values with contemporary student behavior management, providing practical insights for character education in modern Islamic boarding schools.